2019
DOI: 10.1186/s12302-019-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

Developments in society and implications for emerging pollutants in the aquatic environment

Abstract: Pollutant emissions in river basins may be subject to change. How can we succeed in predicting future pollutant emissions and risks? The approach presented here is based on the hypothesis that the existing scenarios on developments in society may provide useful indications on future pollutants. To begin with, the results of four societal scenario-based analyses showed that some developments are directly connected to consumption and the emission of specific substances. Second, it appeared that the effects of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 60 publications
1
31
0
2
Order By: Relevance
“…As medical knowledge grows, the expectation for new pharmaceutical-based treatments for diverse health conditions will continue. A current example is the clear incentive for drug companies to devise more effective compounds to treat a range of age-related conditions (18). Ethinylestradiol has been a very effective oralcontraceptive, but the combination of its potency and persistence made it an important contributor to endocrine disruption in wild fish downstream of wastewater effluent (19).…”
Section: New Chemicals and New Places Of Concernmentioning
confidence: 99%
“…As medical knowledge grows, the expectation for new pharmaceutical-based treatments for diverse health conditions will continue. A current example is the clear incentive for drug companies to devise more effective compounds to treat a range of age-related conditions (18). Ethinylestradiol has been a very effective oralcontraceptive, but the combination of its potency and persistence made it an important contributor to endocrine disruption in wild fish downstream of wastewater effluent (19).…”
Section: New Chemicals and New Places Of Concernmentioning
confidence: 99%
“…In an intermolecular process, the electron flux represents a fundamental parameter to understand the molecular interaction type [85]. The electron flux for each complex was calculated by using Equation (5).…”
Section: Electronic Transference Conceptual Density Functional Theory and Molecularmentioning
confidence: 99%
“…All CBMs use (eco)toxicity and exposure information on the mixture components to assess the risks of chemical mixtures. CBMs are therefore applied after establishing the presence of chemical pollution with chemical screening methods [12], or after prospectively evaluating expected pollution trends [17,30] and possible exposure scenarios that result from the implementation of different abatement strategies [17,31].…”
Section: Requirementsmentioning
confidence: 99%
“…The application of the approach also demonstrated that the risks and relative importance of various compound groups in relation to land use and waste water treatment plants varied [39]. Application to 'think tank' scenarios on future pollution, and evaluation of alternative abatement scenarios, was productive in that it showed which chemical groups and which focus in selecting abatement strategies would reduce predicted impact magnitudes most [30]. These examples also underline how monitoring data (WFD-Annex V) analysed with the CBMs can help to evaluate water quality status and trends.…”
Section: Anticipating the Effects For Future Emission Scenarios And Mmentioning
confidence: 99%